Does the Site of Anterior Tracheal Puncture Affect the Success Rate of Retrograde Intubation? A Prospective, Manikin-Based Study - Eric A. Harris; Kristopher L. Arheart; Kenneth E. Fischler (Anesthesiology Research and Practice)
Background. Retrograde intubation is useful for obtaining endotracheal access when direct laryngoscopy proves difficult. The technique is a practical option in the “cannot intubate / can ventilate” scenario. However, it is equally useful as an elective technique in awake patients with anticipated difficult airways. Many practitioners report difficulty successfully advancing the endotracheal tube due to anatomical obstructions and the acute angle of the anterograde guide. The purpose of this study was to test whether a more caudal tracheal puncture would increase the success rate. Methods. Twenty-four anesthesiology residents were randomly assigned to either a cricothyroid or a cricotracheal puncture group. Each was instructed how to perform the technique and then attempted it on a manikin at their assigned site. Data collection included whether the trachea was intubated, the number of attempts required, and the total time. Results. Both groups displayed a high degree of success. While the group assigned to the cricotracheal site required significantly more time to perform the procedure, they accomplished it in fewer attempts than the cricothyroid group. Conclusion. Retrograde intubation performed via a cricotracheal puncture site, while more time consuming, resulted in fewer attempts to advance the endotracheal tube and may reduce in vivo laryngeal trauma.